DISPERSION AND TRACES: AUDIOVISUAL FILES IN CUATREROS (ALBERTINA CARRI, 2016) - Dávila, Ignacio Del Valle; Seliprandy, Fernando (Revista de Historia Social y de las Mentalidades, 2024)
The article analyzes the uses of audiovisual and written archives in the film Rustlers (2016) by Argentinean filmmaker Albertina Carri. Years after The blonds (2003), she reflects once again on the memory of the authoritarian past of her country, but this time crossing a subjective search in voice over with the visual heritage of the 1970s. The book Isidro Velázquez: formas prerrevolucionarias de la violencia, published in 1968 by his father, the disappeared sociologist Roberto Carri, is the starting point around which personal questions and heterogeneous archival materials gravitate. Our hypothesis is that in Rustlers there is a dialectic between dispersion and aesthetic form, ruin and trace that unfolds in an archival kaleidoscope that reframes that history of violence.
Keywords: Archive; Movies; Memory; Children